Analisis Peran Dan Fungsi Badan Pertimbangan Dan Pengawasan Pelayanan Jemaat (BPPPJ) Sebagai Audit Internal Pada Gereja Masehi Injili Di Timor (Studi Kasus Pada Gmit Imanuel Batukadera Kupang) - Gherald Pranata Alomau; Herly Mathelda Oematan; Yemima Eka Christi Windya (STIE AMKOP, 2025)
This study aims to analyze the role and function of the Congregational Service Advisory and Oversight Board (Badan Pertimbangan dan Pengawasan Pelayanan Jemaat or BPPPJ) as the internal audit body within the Evangelical Christian Church in Timor (Gereja Masehi Injili di Timor or GMIT), Imanuel Batukadera Congregation. A qualitative descriptive approach was employed, using in-depth interviews and document analysis involving BPPPJ officials and congregational financial managers. The findings indicate that the BPPPJ has carried out its oversight and advisory functions in accordance with GMIT's internal oversight guidelines. However, financial reporting has yet to meet national reporting standards and therefore does not fully reflect the congregation's asset position. These findings underscore the need to strengthen the role of BPPPJ within a governance and accountability framework, so that internal audit in churches functions not only as an administrative control mechanism but also as a tool to enhance public accountability. This study reinforces GMIT’s internal oversight system and advances the internal audit concept in faith-based nonprofits.